Dealing with delayed onset muscle soreness (DOMS): foam roller or mechanical manipulation of body tissue - Mohamad Nizam Nazarudin; Mohd Firdaus Abdullah; Mohd Radzani Abdul Razak; Abu Yazid Abu Bakar; Denise Koh Choon Lian; Wan Ahmad Munsif Wan Pa (Horizon Research Publishing, 2021)
This research focuses on determining the efficacy of sports massage (SM) and foam rolling (FR) to decrease Delayed Onset Muscle Soreness (DOMS) among users of recreational gyms. The goal of this study is to fit the physiotherapist's more efficient technique or techniques to scale back DOMS. SM and FR are two factors that help to illustrate the efficacy of DOMS scale back. Both therapies, SM and FR party, were handled with the selected samples for this analysis. Repeated measure ANOVA was used for testing results on the impact of SM on the range of motion (ROM). Results showed the effect of SM on pain meter supported on three occasions, and the effect of froth rolling on the pain meter on three times. Results suggest that there are not substantially different effects between therapies for all elbow flexion ranges of motion. Both therapies are often used to minimize DOMS due to growth over a 3-fold duration. The researcher has dressed up a couple of the guidelines and ideas required for future studies to be used. Future research should refer to the feminine community to boost the performance.